Molecular Characterization of the Archaeal Community in an Amazonian Wetland Soil and Culture-Dependent Isolation of Methanogenic Archaea - Siu M. Tsai; Rosana F. Vazoller; Jeanedy M. Pazinato; Lucas W. Mendes; Ezio N. Paulo (Diversity, 2010)
Tropical wetlands are the major natural source of methane released into the atmosphere, producing about 60% of all natural emissions. The great wetland areas of the Amazon basin are the largest source of methane in this region, contributing an estimated 5% of the total emissions from the world’s flooded areas. However, despite the important role that methanogenic archaea play in these environments, there have been few studies on the composition of their archaeal communities. In this survey, four 16S rRNA archaeal clone libraries from different depths were constructed to examine the archaeal community in an Amazon wetland soil. A total of 599 clones were used to perform diversity and phylogenetic analyses. A broad, diverse archaeal community was found at the site, with the diversity decreasing as the depth increased (Shannon index range: 2.40–1.94). Phylogenetic analysis revealed sequences belonging to two archaeal phyla, with 65% classified as Crenarchaeota and 35% classified as Euryarchaeota. Within the Euryarchaeota group, most sequences were clustered into the Methanococci and Methanomicrobia classes, two groups of methanogens. Based on the abundance of methanogenic organisms, culture–dependent isolation was used to isolate these organisms. To enhance the growth of methanogenic archaea, a modified atmosphere (H2:CO2 = 80:20) was established combined with an anoxic environment for 18 months. Among the isolates, the genera Methanosarcina and Methanobacterium were detected throughout the anaerobic in vitro cultivation, indicating a possible role for these organisms in methane production. In conclusion, these exploratory molecular and culture–dependent approaches enhance our understanding of the archaeal community and methanogenic archaea living in wetland soils of the eastern Amazon and their role in methane production.